Economics of agricultural development : world food systems and re source use - Norton, George W.; Alwang, Jeffery; Masters, William A. (New York : Routledge, 2021)
"Economics of Agricultural Development examines the causes, severity , and effects of poverty, population growth, and malnutrition in develo ping countries. It discusses potential solutions to these problems, pro gress made in many countries in recent years, and the implications of g lobalization for agriculture, poverty, and the environment. Topics cove red in the book include: Means for utilizing agricultural surpluses to further overall economic development. The sustainability of the natural resource environment. Gender issues in relation to agriculture and res ource use. The contribution of improved technologies to agricultural de velopment. The importance of agricultural policies and institutions to development and trade. Actions to encourage more rapid agricultural and economic development This new edition reflects the following developme nts: Growth in environmental challenges due to climate change. Continue d progress in agricultural and economic development in many low-income countries while other countries and regions are being left behind. Cont inued growth in demand for higher-valued farm products This book is ess ential reading for undergraduate students seeking to understand the eco nomics of agricultural development and the world food system, including environmental and human consequences, international trade, and capital flows. It contains a wealth of real-world case studies and is accompan ied by a website"--
Revised edition of the authors' Economics of agricultural developmen t, 2015.
Includes bibliographical references and index.
Keywords: Agriculture -- Economic aspects